Saraca asoca (Roxb.) de Wilde, a sacred tree: Its nutritional value, elemental composition and anti-nutritional content - Suresh, M; Pappuswamy, M (Plant Science Today, 2024)
The sacred Saraca asoca (Roxb.) de Klilde tree holds significant medicinal value and is utilized in ayurvedic preparations to treat various health conditions. This research investigated the nutritional, elemental and anti-nutritional properties of S. asoca leaves and flowers. The nutritional qualities of the tree parts were examined using the muffle furnace and micro-Kjeldahl techniques. Titration techniques were used to assess the anti-nutritional content of plants, whereas EDX (Energy dispersive X-ray) was used to determine the mineral content. Phytochemical analysis revealed the presence of tannins, phenols and flavonoids, along with antioxidant properties that could neutralize free radicals generated by metabolic processes in the body. Nutritional analysis indicated that the floral parts of S. asoca had higher moisture, carbohydrate and crude fat content than the leaves. Conversely, the leaves had elevated ash levels, crude fiber and protein. Leaf samples showed higher concentrations of minerals like calcium, phosphorus, sodium, iodine, iron and manganese compared to the floral samples. In contrast, flower samples exhibited higher potassium, copper, silicon and zinc levels. These findings highlight the rich nutritional profile, abundant phytochemicals and essential minerals in both tree parts, with low anti-nutrient content. This information could be instrumental in developing phytopharmaceuticals and nutritious food products. Additionally, utilizing these tree parts could offer a cost-effective way to enhance nutrient intake and address nutritional deficiencies in humans and animals.